Evaluation of Iypathi Chooranam - A Review of its Therapeutic Potential - K. Ramya,; G. Pandipriya,; A. Anbumalar,; T. Maharasi Maniselvi, (International Journal of Ayurveda and Pharma Research, 2025)
Siddha medicine is one of the traditional originating from south India, offers a unique approach to the diagnosis and treatment of eye disease (Kannoigal), based on the foundational concepts of Pancha bootham and three bodily humours (Vali, Azhal, Iyyam). The medicine called Iypathy Chooranam is one among the siddha medicine mentioned on the book Agasthiyar nayana vithi. The drug review of the medicine explains about morphology, family, chemical constituents and pharmacological actions of each ingredient. The main sources of review as siddha text and resources from the database and relevant journal. The main aim of the study is to evaluate the chemical characters and action of the drug Iypathi chooranam. Secondary aim is to spread consciousness about the drug. The conclusion suggest Iypathi chooranam may possess therapeutic benefits, but further research is needed to establish its efficacy and safety.